Azziy Enterprise / Nurul Izatie Zainal Akmar - Zainal Akmar, Nurul Izatie; Azman, Saidatul Nur Atieka; Ya'acoub, Zaizura; Zulkifly, Zureen Atieqa; Ishak, Hayati (2018)
To apply for a loan of RM 250,000 from SME Bank (get from sources of finance). This business will be manage by four workers which are general manager, social media assistant (2) and account manager.